KEGIATAN MEMBUAT APE PLAYDOUGH UNTUK MENGOPTIMALKAN PEMBELAJARAN DI PAUD CERIA KEC. WAY JEPARA KAB. LAMPUNG TIMUR - Anita Oktaviana (LPPM STAI Darussalam Lampung, 2024)
Educational game tools (APE) for early childhood are always designed with deep thought according to the characteristics of the child and adapted to the child's age range. The aim of this research is to increase teacher creativity in making educational game tools at PAUD Ceria Way Jepara. This assistance is carried out using the service learning method, namely the accompanying team provides materials and guides children at PAUD Ceria Way Jepara to practice making playdough educational games. Community service by STAI Darussalam Lampung lecturers has provided the following results: a) Increased knowledge and understanding of easy learning procedures using APE Playdogh, b) Increased student skills.